An Ethically Justified Approach That Integrates Advance Directives Discussions With Care of the Patient With Cancer. (December 2021) - Patel, Rima; Mathew, Paul
Although the frequency of advance directives discussions may be increasing, there is a need to improve the quality of these discussions. In a range of advanced medical illnesses, including cancer, poor outcomes with advanced cardiopulmonary life support (ACLS) have been well documented. However, when speaking to patients at the end-of-life, physicians frequently withhold evidence-based information and guidance about prognosis or outcomes of ACLS. Tools and models developed to facilitate communication at the end-of-life do not explicitly include recommendations on advance directives and specifically do not discuss the available evidence on ACLS outcomes in the seriously ill. Here, we review the current literature on outcomes of ACLS and current tools and communications for end-of-life discussions. A majority of patients have a preference for truth-telling and guidance. We advocate an approach that integrates individual goals and preferences with a shared understanding of prognosis and appropriate management options, as judged and recommended by the disease experts, in order to reach an evidence-based decision on advance directives. This pragmatic and ethically justified approach emphasizes active empathic communication to prioritize the care of the patient over the mechanical details of ACLS, thereby aligning end-of-life discussions with current practices in other domains of medicine.